Neighbour effects in the provision of public goods in a young democracy: Evidence from China - Agostini, Claudio A.; Brown, Philip; Zhang, Xiaobo (Wiley, 2016)
Fiscal mimicking and yardstick competition among neighbouring jurisdictions have been widely documented in developed countries with long histories of democracy. However, there is very little empirical evidence concerning these practices in developing countries with young democracies. Using a primary panel of 86 rural Chinese administrative villages that have undergone transitions to democracy over the past two decades, we show that the neighbourhood effect also exists in a young democracy, albeit at a lower magnitude than in a mature democracy. Elected chairs of village committees who have served more than one term respond positively to the provision of public projects in neighbouring villages by increasing both the number of public projects and the funding allocated to undertake them. In contrast, appointed party secretaries with more than 1 year of service are insensitive to neighbours' performance. In addition, village leaders are strategic in timing the arrival of public projects to increase the probability of re‐election: in the year preceding elections, both the number and budget of public projects increase significantly. In this sense, politicians in young and old democracies behave alike.